Exchange rate misalignment, volatility and import flows in Malaysia - Mohd Naseem, Niaz Ahmad; Tan, Hui Boon; Mohd, Siti Hamizah (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This paper investigates the effect of real exchange rate misalignment and volatility on Malaysian import flows during 1991:Q1 to 2003:Q4. A measure of the quantitative proxy of the real exchange rate misalignment is constructed using the Natural Real Exchange Rate (NATREX) equilibrium model, whereas the volatility of real exchange rate is generated from the GARCH model. This paper differs from existing literature as the effects of exchange rate misalignment significantly hastened the level of Malaysian imports for period of the study. The empirical results also show that the exchange rate volatility has merely promoted the Malaysian imports during the crisis period. This suggests that the exchange rate misalignment and volatility are important determinants in inspiring Malaysian import flows, especially during the 1997 Asian financial crisis.